Nearpod As a Means of Promoting Students’ Engagement in English Class - Efendi, Tri Achmad (Borneo Journal of Language and Education, 2024)
Merdeka curriculum has been implemented as a means to adapt to the situation and challenges of the 21st century. Two of the 21st century teaching and learning characteristics are the technology integration and student-centeredness. High engagement in the process of teaching and learning is the indicator of the 21st century education runs well. However, Indonesian students, at the school under the study, the engagement was low and students were passive. Therefore, this research was aimed at figuring out the use of Nearpod as a means of promoting students’ engagement as well as it was attempted to find out the students’ perceptions of Nearpod in the teaching and learning process to gain feedback on the students’ acceptance and Nearpod usefulness in language teaching and learning. This research was conducted at SMAN 1 Menganti, Gresik. There were 49 students as participants in this study. In order to seek the data, this research employed a qualitative experimental design with a field note, a questionnaire, and FGD as the instruments. Then, the data were analyzed with thematic analysis. The findings indicated that Nearpod could be used as a means of promoting students’ engagement unless it is supported with the stable internet connection, and the students perceived neutral opinion regarding the use of Nearpod.